2017
DOI: 10.1016/j.apj.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Stability of autobiographical memory in young people with intellectual disabilities

Abstract: The present study aimed to analyze the stability of the memory of a stressful event (medical examination within a hospital setting) over time in young people (age range 12 to 21, M age = 15.11 years old, SD = 3.047) with mild or moderate intellectual disability (IQ = 54.32, SD = 13.47). The results show a stability of the memory of what happened an hour and a week after the event in relation to the people involved, the apparatus used, and the parts of the body explored. No interaction effects were found betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…2017 data collection occurred later than was ideal due to the 'snap' election. While the validity of the 2017 template was confirmed by the 2019 data (collected closer to that election), 2017 data quality was potentially limited by forgetting – although the common assertion that people with intellectual disabilities have particularly impaired long‐term memory is challenged as oversimplistic and reductive, with factors like verbal IQ (Morales et al, 2017) and intellectual disability type (Vicari et al, 2016) shown to influence individual memory performance.…”
Section: Discussionmentioning
confidence: 98%
“…2017 data collection occurred later than was ideal due to the 'snap' election. While the validity of the 2017 template was confirmed by the 2019 data (collected closer to that election), 2017 data quality was potentially limited by forgetting – although the common assertion that people with intellectual disabilities have particularly impaired long‐term memory is challenged as oversimplistic and reductive, with factors like verbal IQ (Morales et al, 2017) and intellectual disability type (Vicari et al, 2016) shown to influence individual memory performance.…”
Section: Discussionmentioning
confidence: 98%
“…This qualitative investigation relied on people's memories to describe their past experiences with interviews conducted after the hospital stay. Memory is both changeable and constructed (Barusch, 2011; Blakey et al., 2019; Young Rojahn, 2013), and the accuracy of memory of people with intellectual disabilities has often been questioned (Morales et al., 2017). However, Cohen et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2010) contend that what people remember is significant to them and it has been acknowledged that assumptions should not be made that the memory of people with intellectual disabilities is poor; Morales et al. (2017) demonstrated that emotional memory of hospital experiences in people with intellectual disabilities are stable over time. Blakey et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies (Manzanero, Contreras, Recio, Alemany, & Martorell, 2012) have shown that people with ID may perform approximately the same as others in forensic contexts. Moreover, their autobiographical memories may be quite stable over time, being their ability to describe an event independent of the degree of disability (Morales et al, 2017). Indeed, Henry et al (2011) found no correlation between credibility assessment and either witness mental age or anxiety.…”
Section: El Análisis De Contenido Basado En Criterios En Víctimas Reamentioning
confidence: 97%